2021
DOI: 10.1002/eji.202048977
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized multicellular crosstalk in lymph nodes coordinates the generation of potent cellular and humoral immune responses

Abstract: Distributed throughout the body, lymph nodes (LNs) constitute an important crossroad where resident and migratory immune cells interact to initiate antigen-specific immune responses supported by a dynamic 3-dimensional network of stromal cells, that is, endothelial cells and fibroblastic reticular cells (FRCs). LNs are organized into four major subanatomically separated compartments: the subcapsular sinus (SSC), the paracortex, the cortex, and the medulla. Each compartment is underpinned by particular FRC subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 155 publications
0
6
0
Order By: Relevance
“…In summary, our understanding of mechanisms by which LNs determine the fate of alloimmune responses has evolved markedly following prior advances that have been made to understand more deeply the functions of specific cellular and stromal components of the LN ( 7 , 79 , 81 , 131 ). The data from these studies could lay the groundwork to develop innovative therapeutic strategies aimed at manipulating the microenvironment within LNs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, our understanding of mechanisms by which LNs determine the fate of alloimmune responses has evolved markedly following prior advances that have been made to understand more deeply the functions of specific cellular and stromal components of the LN ( 7 , 79 , 81 , 131 ). The data from these studies could lay the groundwork to develop innovative therapeutic strategies aimed at manipulating the microenvironment within LNs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified various subclasses of FRCs that comprise the stromal compartments within the different regions of the LN. FRCs in the LN paracortex are important for supporting the interactions between DCs and T cells (7,79). FRCs provide this support in several ways, including maintenance of HEV integrity, promotion of entry of naive T cells into the LN, and generation of a stromal compartment that supports the mechanical interaction between DCs and T cells (7,(79)(80)(81).…”
Section: Discussionmentioning
confidence: 99%
“…Up to 75% of immature B cells possess a nonfunctional or self-reactive BCR and undergo clonal deletion or receptor editing [ 31 ]. Transitional B cells that successfully produce functional and non-self-reactive BCR exit bone marrow, enter the blood, and migrate to secondary lymphoid organs (SLO) [ 32 ]. In the periphery, B cells continue their development and, since transitional B are short-lived cells, rapidly differentiate into mature-naïve B cells.…”
Section: Background Of B Lymphocytesmentioning
confidence: 99%
“…The LN is poised to rapidly respond to immune challenge through the strategic positioning of LN stroma and resident innate immune cells, located to best capture incoming lymph‐borne particulate material 9‐11 . In the steady state, macrophages line the subcapsular sinus (SCS) floor and trap antigen, immune complexes, and viral particles and can deliver these antigens to follicular B cells 12‐14 .…”
Section: Spatial Preference For Activation In the Lnmentioning
confidence: 99%
“…The LN is poised to rapidly respond to immune challenge through the strategic positioning of LN stroma and resident innate immune cells, located to best capture incoming lymph-borne particulate material. [9][10][11] In the steady state, macrophages line the subcapsular sinus (SCS) floor and trap antigen, immune complexes, and viral particles and can deliver these antigens to follicular B cells. [12][13][14] Similarly, DCs (of the cDC2 subset) line the lymphatic sinuses for rapid particulate antigen capture, 15,16 while other DCs position along the LN conduit network for soluble antigen uptake in the paracortex.…”
Section: S Patial Preferen Ce For Ac Tivati On In the Lnmentioning
confidence: 99%